Alternative approaches to the calculation of nutrient density. (17th October 2014) - Kennedy, Eileen; Racsa, Patrick; Dallal, Gerard; Lichtenstein, Alice H; Goldberg, Jeanne; Jacques, Paul; Hyatt, Raymond
Abstract : A renewed interest in promoting health and wellness has prompted both public- and private-sector organizations to adopt systems for rating the nutritional quality of individual food products. Compared here are three food quality scores for ranking foods. The absolute score varies by the food quality score algorithm used, but the relative ranking of foods within a food group is stable. Fruits and vegetables are substantially more nutrient-dense than items from other food groups. There is an imperative need for a simple, consistent method to guide consumers in making healthier food choices.